Supportive Environment for Teaching and Learning Digital Image Processing - Silva, Lenon Fachiano [UNESP]; Olivete Junior, Celso [UNESP]; Reis, Pedro Henrique [UNESP]; Santos, Rafael Silva [UNESP]; Messias Correia, Ronaldo Celso [UNESP]; Garcia, Rogerio Eduardo [UNESP]; IEEE (Ieee, 2015)
Digital Image Processing (DIP) consists of a set of techniques to acquire, represent and transform digital images. Through these techniques, it is possible to extract and identify information of images and improve the visual quality by facilitating human perception and interpretation by computer systems. However, the Digital Image Processing teaching is hindered by the complexity of implementation of many techniques, on several occasions is not possible that student visualize the results of DIP techniques when are discussed during the course. This paper presents an experiment over a web platform to support the teaching of digital image processing. The goal of this platform is not replace coding techniques, but allow rapid visualization and experimentation of studied methods, without be necessary to install software or previous knowledge of a specific programming language.
Keywords: Digital image processing; teaching/learning platform; web platform